Immunogenicity and safety of a quadrivalent inactivated influenza vaccine in healthy subjects aged 3 to 17 years old: A phase III, open label, single-arm study. Issue 22 (8th May 2020) - Chang, Chia-Yuan; Cho, Ching-Yi; Lai, Chou-Cheng; Lu, Chun-Yi; Chang, Luan-Yin; Hung, Miao-Chiu; Huang, Li-Min; Wu, Keh-Gong
Highlights: This quadrivalent influenza vaccine was given to subjects 3 to 17 years of age. Immunogenicity was determined by high seroconversion and seroconversion rates. This vaccine is well tolerated with a favorable safety profile. A quadrivalent vaccine may overcome the mismatches with influenza B strains. Abstract: Background: Quadrivalent influenza vaccines are particularly valuable during seasons in which a mismatch occurs between the predicted influenza B lineage for the trivalent influenza vaccine and the circulating strain. This study evaluated the immunogenicity and safety of a quadrivalent inactivated influenza vaccine AdimFlu-S manufactured in Taiwan for the 2016–2017 influenza season in healthy children. Methods: A total of 174 healthy children aged 3 to 17 years old were separated into 3 groups (Group A: 3–8 years old, vaccine naïve; Group B: 3–8 years old, vaccine non-naïve; Group C: 9–17 years old, any vaccine status). Sera was collected pre and post vaccination for each participant. A hemagglutination inhibition (HAI) assay was utilized to calculate geometric mean titer (GMT), seroprotection rate, and seroconversion rate. Results: All enrolled participants completed the study. For the four vaccine strains four weeks after the last vaccination, geometric mean titer ratios (GMTRs) were between 2.9 and 20.9, seroconversion rates were between 42.9% and 90.9%, and seroprotection rates were all above 96.4%. This achieved all immunogenicity endpoints and fulfilled the criteria of the European Medical Agency's Committee for Medicinal Products for Human Use (CHMP). No serious adverse events (AEs) were reported during the follow-up period of 6 months. Conclusion: This quadrivalent influenza vaccine is demonstrated to be well tolerated and displays robust immunogenicity for each influenza strain. This could potentially improve protection against the antigenically distinct B/Yamagata and B/Victoria lineages.